Impotence in Education: Tracing Fragments of Agamben's Philosophy of Education - Pramono, Made (Universitas Airlangga, 2023)
This study aims to discuss Giorgio Agamben's rethinking education theory. In the theory of rethinking education, Giorgio Agamben emphasizes that potential can only be thought of in term of impotence. The results of the discussion find several points. First, when potency and impotency are separated from each other, it can be considered as a graded education system in which some students are instructed to actualize their potential in the form of standardized tests while others are abandoned by the system. Second, thinking impotence allows to rediscover the uniqueness of learning beyond the formulation of learning problems. Thus, without the concept of impotence, the discourse of 'child genius' becomes commodified as a force to be utilized and actualized in the name of neoliberal entrepreneurship. In short, we can reclaim genius and its relation to the issue of educational freedom only by returning to impotence.